2020
DOI: 10.1016/j.jenvp.2020.101412
|View full text |Cite
|
Sign up to set email alerts
|

Facing natural disasters through the endorsement of authoritarian attitudes

Abstract: We analyzed the relations between exposure to news describing a natural disaster and right-wing authoritarianism (RWA) with 241 Italian adults, surveyed twice, before and after a severe earthquake. Our results were compatible with the idea that the exposure to earthquake news led to an increase in RWA among people who had low, but not among who had relatively high, authoritarian levels before the event. We discuss the findings in terms of compensatory control, and highlight strengths and limitations of the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 31 publications
1
16
0
1
Order By: Relevance
“…This conditional shift toward authoritarian attitudes is dependent on the use of authoritarianism as a coping strategy to deal with the uncertainty of threats. Previous studies have observed this pattern in response to different types of societal threats, including criminality, malicious out‐groups threatening social order, and exposure to natural disasters (Mirisola et al., 2014; Russo et al., 2020).…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…This conditional shift toward authoritarian attitudes is dependent on the use of authoritarianism as a coping strategy to deal with the uncertainty of threats. Previous studies have observed this pattern in response to different types of societal threats, including criminality, malicious out‐groups threatening social order, and exposure to natural disasters (Mirisola et al., 2014; Russo et al., 2020).…”
mentioning
confidence: 73%
“…Based on Ben-Zur, Gil, and Shamshins (2012), we believe that a direct exposure to COVID-19 produced a primary traumatization and that those who remained healthy and did not have infected individuals in their social networks suffered a secondary traumatization. Russo et al (2020) showed that secondary traumatization fosters support for anti-democratic political systems. Our study showed that primary traumatization incontrovertibly adds to secondary traumatization, which supports the relevance of the link between personal threat and support for anti-democratic political systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such a situation, people are inclined to have uncritical trust in authority and negative attitudes toward groups that threaten order and stability. This psychological tendency increases people's dependence on the authorities and risks creating room for anti‐democratic leaders and political systems (Jost et al., 2003; Kay et al., 2008; Russo et al., 2020).…”
Section: Social Dominance Orientation and Right‐wing Authoritarianismmentioning
confidence: 99%
“…The literature on the relations between threats and authoritarianism shows that people can react to threats by resorting to secondary sources of control, with the function of compensating the loss of direct control over their life and environment (e.g., Kay et al., 2008). Before COVID‐19, the literature mainly focused on the existential threats stemming from natural disasters (e.g., Russo et al., 2020), climate disasters (e.g., Zapata, 2018), and economic crises (e.g., Chen, 2010), showing the role of compensatory sources of control played by religion (e.g., Sibley and Bulbulia, 2012), the government (e.g., Oneal, Lian, and Joyner, 1996), and, most importantly for this study, anti‐democratic authorities (Mirisola et al., 2014). In line with this, more recent studies indicated that the COVID‐19 pandemic has led to an increase in religiousness and church attendance (e.g., Molteni et al., 2021), trust in the government (e.g., Bol et al., 2021), and anti‐democratic attitudes and preferences (e.g., Amat et al., 2020; Roccato et al., 2020).…”
Section: The Covid‐19 Pandemic In Italymentioning
confidence: 99%